Skuldbelydenis en versoening: 'n Ou-Testamentiese perspektief - Olivier, Hannes (Nederduits Gereformeerde Teologiese Tydskrif, 1997)
O. treats the relationship between the confession of guilt and reconciliation as well as the relevance of that relationship for South African theological discourse. He gives particular attention to the semantics of the concepts kipper and ydh (hithpael), arguing that these concepts are intertwined, that they function mainly in a cultic context, and that they are theologically linked to God's forgiveness and mercy. O.'s piece also emphasizes the role of the Dutch Reformed Church in general and the Faculty of Theology of the University of Stellenbosch in particular with regard to the current process of reconciliation in South Africa. [Published abstract–Christopher T. Begg].] Abstract Number: OTA20-1997-OCT-1758
Keywords: Biblical Theology